Perencanaan Pengembangan Modul Pembelajaran Matematika Untuk Warga Belajar Paket C Berbasis Open Source (Scilab) di Pusat Kegiatan Belajar Masyarakat (PKBM) Karang Putih - Heru Dibyo Laksono; Reri Afrianita; Novizon Novizon (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The planning for the development of a mathematics learning module for residents studying package C based on the open-source platform Scilab at the Community Learning Center (PKBM) Karang Putih is one of the solutions to address the lack of facilities, especially open-source learning media. The activity plan started with discussions and information sharing. In this stage, discussions and experiences were shared regarding the Scilab-based mathematics learning module for package C learners. The second activity is the analysis of the module's needs. Based on the discussion's outcomes, decisions will be made about the type of module to be created, the required features, potential challenges, necessary resources for the development process, and so on. The third activity is the design of the learning module. During this phase, the interface and layout of the open-source Scilab-based mathematics learning module are designed. The final activity is the development of the learning module. This stage involves implementing the outcomes of the analysis and design of the mathematics learning module. It also includes testing to ensure that all functions work as intended. By following this planned process, the development of the mathematics learning module for package C learners using Scilab will be expected to provide a valuable open-source learning resource at the Community Learning Center (PKBM) Karang Putih.